KUE TRADISIONAL UBI NANAS SEBAGAI PENGGANTI PENURUN KADAR GULA DARAH PADA ORANG DEWASA - Indah Risky Siregar (CV. Adiba Aisha Amira, 2023)
Cassava is rich in carbohydrates and is a staple food for dry or barren regions of Indonesia. The tubers are cooked for various types of food such as boiled or fried cassava, tapai and others. So it has the most important economic meaning compared to other types of tubers. Pineapple (Ananas Comosus L. Merr) is a very popular fruit in Indonesia which has a very high nutritional value compared to other fruits. Pineapple has the advantage of helping health because it contains the enzyme bromelain, which hydrolyzes protein, tenderizes meat, and has healing properties. Traditional pineapple cake is a cake made from cassava with the addition of pineapple covered with grated coconut. Processed cake is very high value. Pineapple sweet potato is a food that is in great demand by the public because it tastes sweet, savory, and has a variety of flavors. Pineapple sweet potato is also a food that can help reduce blood sugar levels because sweet potatoes can be used as a substitute for rice in adults who want to lower blood sugar levels. Pineapple sweet potato is a food that can be a solution for lowering blood sugar levels.